Group‐level competition influences urinary steroid hormones among wild red–tailed monkeys, indicating energetic costs. Issue 5 (10th April 2018) - Jaeggi, Adrian V.; Trumble, Benjamin C.; Brown, Michelle
Abstract : Various theories emphasize that intergroup competition should affect intragroup cooperation and social relationships, especially if the cost of inter group competition outweighs that of intra group competition. This cost of intergroup competition may be quantified by changes in physiological status, such as in the steroid hormones cortisol (C) and testosterone (T), which rise or are depressed during periods of energetic stress, respectively. Here we tested for changes in urinary C and T after intergroup encounters (IGEs) among wild red‐tailed monkeys ( Cercopithecus ascanius ), a species that experiences frequent intergroup feeding competition, at the Ngogo station in Kibale National Park, Uganda. We assayed 108 urine samples, of which 36 were collected after IGEs, from 23 individuals in four social groups. Bayesian multilevel models controlling for various confounds revealed that IGEs increased C and decreased T relative to baseline, consistent with an energetic cost to IGEs. The C change was more apparent in samples collected early after IGEs, suggesting an anticipatory increase, whereas the T change was stronger in later samples, suggesting sustained energetic trade‐offs. Hormone responses were not affected by the IGE outcome. This cost to intergroup competition, together with little evidence for intragroup competition in redtails and other guenons, establishes an interesting test case for theories emphasizing the effect of intergroup competition on intragroup cooperation. Abstract : We measured steroid hormone responses of wild redtail monkeys to intergroup competition. We found increases in cortisol and decreases in testosterone, highlighting the energetic cost of intergroup competition. This cost to intergroup competition, together with a lack of evidence for within‐group competition in this species provides an interesting test case for theories emphasizing the role of group‐level competition on within‐group relationships.